KOLABORASI MULTI ACTOR DALAM PENGEMBANGAN WISATA BUKIT ANJHIR (STUDI KOLABORASI DESA ALANG-ALANG DAN DESA KEMUNING) - Citra Rengganis; Hisnuddin Lubis (DIMENSI - Jurnal Sosiologi, 2023)
Bukit Anjhir is located in Kemuning Village, Tragah District, Bangkalan Regency. To reach Bukit Anjhir, the main access road passes through Alang-alang Village. This hill has great potential to be developed as a tourist destination. However, unfortunately, the potential of Bukit Anjhir has not been fully utilized by the local community there. Therefore, with this research, it is hoped that the communities of Kemuning Village and Alang-Alang Village will be motivated to collaborate in developing the management of Bukit Anjhir as a tourist attraction. This research uses a qualitative research method with a case study approach. Informants were selected using purposive sampling technique. Data collection methods included observation, interviews, and documentation. The data obtained will be analyzed using Miles and Hubberman's analysis techniques, and the validity of the data will be checked using source triangulation. The results of this research show that the appropriate form of collaboration in managing Bukit Anjhir as a tourist destination is by dividing tasks between the two villages and forming a cooperative, namely KSUP BUKIT ANJHIR, which consists of a combination of tourism-aware groups from both villages.